KADERISASI PEREMPUAN PARTAI POLITIK ( Studi Pada Partai Golkar dan PKB Provinsi Riau Tahun 2009-2014) - Muharni "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Political parties play a very important role in a democratic system. Political parties are important institutions in efforts to increase women's representation in politics. The low representation of women in politics and the low commitment of political parties in empowering women cadres is an interesting issue to study. This is due to the process of screening, screening and the determination of candidates for political office in the hands of the party. The condition of women's representation in the legislature is inseparable from the internal situation of political parties, especially the issue of recruitment and regeneration.This study aims to determine the pattern of cadre carried out by the DPD of the Golkar party and the PKB DPW in Riau Province in the period 2009-2014 and to find out the supporting factors and inhibitors of cadre carried out by the two major parties towards internal party cadres, especially for women cadres in an effort to strengthen quality of politics and increasing representation of women in the political world, especially in the legislature. This study uses qualitative research methods with descriptive types of research. This method aims to get a true picture of the implementation of the regeneration function held by the DPD of the Golkar Party and the DPW of the Riau Province National Awakening Party, especially for women cadres. The method used is the interview method, and documentation of the data obtained is analyzed carefully.The results obtained in this study are 1) There is no specific distinction between recruiting new members and recruitment of legislative candidates conducted both in the Golkar party and PKB for female cadres and male cadres, both of which are open. 2) In terms of regeneration, the Golkar party tends to be more active in carrying out regeneration activities compared to PKB in 2009-2014. 3) To carry out regeneration for women cadres inside the Golkar party formed a wing organization called the Golkar Party Women's Union while PKB formed an Autonomous Agency called Perempuan Bangsa. 4) The main obstacle in this cadre is that the system of the party in question is still not well planned, both regarding cadre and funding instruments so that the impact on the implementation of regeneration is less than optimal.Keywords: Women's Cadreization, Political Parties, Legislative